2014
DOI: 10.1128/aac.02047-13
|View full text |Cite
|
Sign up to set email alerts
|

Spread of NDM-1-Producing Enterobacteriaceae in a Neonatal Intensive Care Unit in Istanbul, Turkey

Abstract: Twenty-two consecutive carbapenem-resistant enterobacterial isolates were recovered from patients hospitalized between January and April 2013 in different units at a university hospital in Istanbul, Turkey. These were Klebsiella pneumoniae isolates producing the carbapenemases OXA-48, NDM-1, and KPC-2, Enterobacter cloacae isolates producing NDM-1, and Escherichia coli isolates producing OXA-48. Most of the OXA-48-producing K. pneumoniae and all the NDM-1-producing E. cloacae were clonally related. The NDM-1-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 27 publications
2
46
0
3
Order By: Relevance
“…However, decreased resistance rates were observed to piperacillin-tazobactam (45%), ciprofloxacin (36%), gentamicin (30%), levofloxacin (27%), and amikacin (9%). Several studies have shown that K. pneumoniae isolates are resistant to antibiotics such as thirdgeneration cephalosporins, carbapenems, fluoroquinolones, and aminoglycosides [26,27]. Lowlevel resistance to amikacin and gentamicin may be good news in the K.pneumoniae-related infections for our isolates and furthermore, ciprofloxacin and piperacillin-tazobactam resistance is in line with a recent study, 29.9% and 22.3%, respectively [28].…”
Section: Discussionsupporting
confidence: 84%
“…However, decreased resistance rates were observed to piperacillin-tazobactam (45%), ciprofloxacin (36%), gentamicin (30%), levofloxacin (27%), and amikacin (9%). Several studies have shown that K. pneumoniae isolates are resistant to antibiotics such as thirdgeneration cephalosporins, carbapenems, fluoroquinolones, and aminoglycosides [26,27]. Lowlevel resistance to amikacin and gentamicin may be good news in the K.pneumoniae-related infections for our isolates and furthermore, ciprofloxacin and piperacillin-tazobactam resistance is in line with a recent study, 29.9% and 22.3%, respectively [28].…”
Section: Discussionsupporting
confidence: 84%
“…However, these antibiotics frequently show unfavourable pharmacokinetics and adverse effects, mainly in patients with underlying conditions. NDM-1-producing Enterobacteriaceae, in particular K. pneumoniae and Enterobacter cloacae, have been previously reported in Istanbul, Turkey (Poirel et al, 2012(Poirel et al, , 2014. NDM-1-producing K. pneumoniae was probably imported into Turkey from Iraq (Poirel et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…Infections caused by carbapenemresistant Enterobacteriaceae in infants and children are of great concern, as these individuals do not tolerate the various available agents, which frequently makes carbapenems the last-resort therapeutic option for treating severe infections in children. Curiously, reports of pediatric outbreaks caused by ST14 were found in Italy, where isolates carried FOX-7 AmpC ␤-lactamase (46); in Tanzania, where isolates carried the ESBL CTX-M-15 (50); and in Turkey, where isolates carried NDM-1 (48).…”
Section: Discussionmentioning
confidence: 99%